APPLICATION OF MECHANICAL CORN SHELLING MACHINE TO THE CORN FARMING COMMUNITY OF BIBIOSI VILLAGE ARSO SWAKARSA DISTRICT KEEROM DISTRICT - Pagasis, Thomas; Mangallo, David; Allo, Rombe; Tambing, Enos; Rantepulung, Selyus; Kaiway, Mickael Ruben (LPPM Univ. Ibn Khaldun Bogor, 2025)
The application of corn shelling machine technology aims to increase the productivity of partner farmers in Bibiosi Village, Keerom Regency so that they can improve their welfare. The target to be achieved is the adoption of corn shelling technology which works mechanically by the target community, increasing corn shelling production and community income, as well as establishing intensive cooperation between Cenderawasih University as the producer and developer of appropriate technology, the community using the technology and the local government. The method used to achieve this goal is by providing a technological touch to the community in processing corn harvests so that corn production can be optimized through the mechanical shelling process of corn. Application of appropriate technology in the form of a corn shelling machine using a petrol motor with 5.5 HP power. Based on the performance test results, this corn shelling machine has a production capacity of 1000 kg/hour. This is expected to help corn farmers to produce shelled corn more quickly and save energy. The application of appropriate technology will have an impact on the welfare of the community in the community partnership program. Apart from that, the application of science and technology is a solution for farmer groups in building insight and mindset in society.